2022
DOI: 10.3389/fphar.2022.793525
|View full text |Cite
|
Sign up to set email alerts
|

Total Triterpenes of Wolfiporia cocos (Schwein.) Ryvarden & Gilb Exerts Antidepressant-Like Effects in a Chronic Unpredictable Mild Stress Rat Model and Regulates the Levels of Neurotransmitters, HPA Axis and NLRP3 Pathway

Abstract: Purpose:Wolfiporia cocos is frequently used in traditional Chinese medicine to treat depression. However, antidepressant-like effects of the main active ingredients of Wolfiporia cocos, total triterpenes of Wolfiporia cocos (TTWC), are not well studied. This study aimed to investigate those effects and explore their specific mechanisms of action in depth.Methods: Chemical components of TTWC were analyzed using LC-MS. Depression-like behavior in rats were induced by chronic unpredictable mild stress (CUMS). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…It was found that upregulation of pro-inflammatory cytokines (IL-6 and TNF-α) was seen in the hippocampus and cortex of Lipopolysaccharide (LSP)-induced depressed mice (17). Inflammatory cytokines in the blood can activate the hypothalamic-pituitary-adrenal (HPA) axis, and HPA dysfunction leads to corticotropin releasing hormone (CRH), adrenocorticotropic hormone (ACTH), increased secretion of corticosterone (CORT) and its negative feedback dysfunction, upregulate the release of glucocorticoids(GC) and cortisol in the adrenal cortex as well as cause dysregulation of monoamine transmitters, while inflammatory factors decrease the release of glucocorticoids and cortisol through activation of indoleamine-2,3-dioxygenase (IDO) enzyme, IDO activation reduces tryptophan and increases toxic metabolites of the kynurenine pathway, which leads to damage to astrocytes, microglia, and neurons, triggering neuroinflammation, which is positively associated with Major Depressive Disorder (MDD) (18)(19)(20). In addition, inflammatory factors can also induce damage to the blood-brain barrier (BBB) and enter the brain (21,22).…”
Section: Cyclo-oxygen-ase-2 Roles In the Pathogenesis Of Depression N...mentioning
confidence: 99%
“…It was found that upregulation of pro-inflammatory cytokines (IL-6 and TNF-α) was seen in the hippocampus and cortex of Lipopolysaccharide (LSP)-induced depressed mice (17). Inflammatory cytokines in the blood can activate the hypothalamic-pituitary-adrenal (HPA) axis, and HPA dysfunction leads to corticotropin releasing hormone (CRH), adrenocorticotropic hormone (ACTH), increased secretion of corticosterone (CORT) and its negative feedback dysfunction, upregulate the release of glucocorticoids(GC) and cortisol in the adrenal cortex as well as cause dysregulation of monoamine transmitters, while inflammatory factors decrease the release of glucocorticoids and cortisol through activation of indoleamine-2,3-dioxygenase (IDO) enzyme, IDO activation reduces tryptophan and increases toxic metabolites of the kynurenine pathway, which leads to damage to astrocytes, microglia, and neurons, triggering neuroinflammation, which is positively associated with Major Depressive Disorder (MDD) (18)(19)(20). In addition, inflammatory factors can also induce damage to the blood-brain barrier (BBB) and enter the brain (21,22).…”
Section: Cyclo-oxygen-ase-2 Roles In the Pathogenesis Of Depression N...mentioning
confidence: 99%
“…To prepare the stock solution [22,23], about 1 mg reference compound (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) was individually dissolved in ACN /water (9:1, v/v). Subsequently, these standard stock solutions were mixed at concentrations of 10.44, 37.12, 54.…”
Section: Preparation Of the Sample Stock And Standard Solutionsmentioning
confidence: 99%
“…The dwell time was at automatic set by the MultiQuant software 3.0.2(AB SCIEX Corp., Massachusetts, USA). The optimized parent and daughter ions in MRM mode were used to evaluate 19 analytes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The content of targets in all Poria cocos samples was calculated and analyzed by the Analyst 1.6.3 software SCIEX, USA).…”
Section: Uplc Coupled With Triple-quadrupole Linear Ion-ms/ms Conditionsmentioning
confidence: 99%
See 1 more Smart Citation